Inteligencias múltiples y su influencia en el aprendizaje significativo en los niños de educación inicial del subnivel II de la Unidad Educativa Francisco Huerta Rendón - Castillo Navarrete, Ginger Sara (2023)
The present case study titled: Multiple intelligences and their influence on the development of meaningful learning in early education children of the Francisco Huerta Rendón Educational Unit, had the objective of analyzing the influence of multiple intelligences on the development of meaningful learning in children. . Which is based on Howard Gardner's theory where he says that intelligences are human abilities to solve conflicts encountered in a certain environment. These abilities are identified because they can be respectively independent at a significant level from each other. The methodology applied is the non-experimental design, quantitative approach and the level of research is exploratory and descriptive, which helps to know the particularities and characteristics of the phenomenon under study. Through these data, it was concluded that multiple intelligences are a fundamental axis for the meaningful process, because they increase social-logical and cooperative learning capacities in infants, these capacities will allow them to interact with their peers effectively and to solve problems. It is concluded that children develop their cognitive skills based on multiple intelligences and meaningful learning, since it helps them develop their autonomous, participatory and creative abilities.